Answer:
the answer is -30.
Step-by-step explanation:
for each x-value, you will multiply it by -5 to get your y-value. i say this because if y-15 when x=-3, if you divide the x from y (so 15/-3) you get -5 which is the number in which y varies by. so you will take 6 and multiply it by -5 which gives you -30.
Answer:
If Sandy bought a soft drink for 2 dollars that's 2 dollars subtracted from the total of $12.00 spent
If we have 10 dollars and bought 5 candy bars we would divide so 10 divided by 5 = 2 so each candy bar costed $2 dollars
Answer:
Step-by-step explanation:
hg(x) means you multiply h(x) times g(x) and then we will set it equal to .
hg(x) = which simplifies to
. Now set that equal to :
and get everything on the same side and factor:
. Factor by grouping:
and factor out what's common in each set of ( ):
which factors out to
. But factors somoe to:
(x + 1)(x - 1)(x - 1) = 0 So the solutions for this are
x = -1, 1
Answer:
Roots of the equation (x+3)(x+5)=0:
−3, multiplicity 1.
−5, multiplicity 1.
Step-by-step explanation:
5.
the equation looks like:
((2x+1)+4)/((x)+4)= 5/3
then you do cross multiplication and get:
6x+3+12=5x+20
subtract 5x on each side. subrtract the 3 and 12 from the 20.
and you get your answer 5=x